2011
DOI: 10.1631/jzus.b1000165
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of cucumber (Cucumis sativus L.) endophytic fungi as seed treatment agents against root-knot nematode Meloidogyne incognita

Abstract: Seed treatment with endophytic fungi has been regarded as an effective method for plant parasitic nematode control. Endophytic fungi from cucumber seedlings were isolated and screened for their potential to be used as seed treatment agents against Meloidogyne incognita. Among the 294 isolates screened, 23 significantly reduced galls formed by M. incognita in greenhouse test. The 10 most effective isolates were Fusarium (5), Trichoderma (1), Chaetomium (1), Acremonium (1), Paecilomyces (1), and Phyllosticta (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 19 publications
0
58
0
Order By: Relevance
“…Such findings could be useful in promoting research aimed at the development of new mosquito control agents, based on bioactive chemical compounds from indigenous fungus sources as an alternative to chemical larvicides. According to Yan et al (2011), endophyte fungi have been shown to protect their hosts against insect pests, pathogens, and even domestic herbivores. These include Aspergillus flavus (Link) and Penicillium sublateritium (Biourge) (Webber 1981), which live and feed on the host plant and, in turn, produce functional metabolites that enhance its fitness and resistance against stresses (Rana et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Such findings could be useful in promoting research aimed at the development of new mosquito control agents, based on bioactive chemical compounds from indigenous fungus sources as an alternative to chemical larvicides. According to Yan et al (2011), endophyte fungi have been shown to protect their hosts against insect pests, pathogens, and even domestic herbivores. These include Aspergillus flavus (Link) and Penicillium sublateritium (Biourge) (Webber 1981), which live and feed on the host plant and, in turn, produce functional metabolites that enhance its fitness and resistance against stresses (Rana et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic fungi have been isolated from a variety of healthy plant species ranging from crops (Fisher et al 1992;Larran et al 2002;Kim et al 2007;Usuki and Narisawa 2007;Yuan et al 2010;Yan et al 2011), invasive plants (Mei et al 2014), woody tree species -especially medicinal plants - Rhoden et al 2012;Wu et al 2013a), mosses (U'Ren et al 2010, ferns (Del Olmo-Ruiz and Arnold 2014), and also lichens (U'Ren et al 2010). In general, Alternaria, Colletotrichum, Fusarium, Gibberella, Glomerella, Guignardia, Leptosphaerulina, Nigrospora, Phoma, Phomopsis and Xylaria are the genera most commonly isolated (Table 1).…”
Section: Biodiversity Of Endophytic Fungimentioning
confidence: 99%
“…Some species such as P. capitalensis are endophytes and weak pathogens (Baayen et al 2002;Glienke et al 2011;Wikee et al 2013a), while others such as P. cocoicola are saprobes (Punithalingam 1974;Taylor and Hyde 2003). Phyllosticta species have been also used as bio-control agents and produce novel bioactive metabolites such as phyllostine and phyllostoxin (Yan et al 2011;Evidente et al 2008a, b;Wikee et al 2011Wikee et al , 2013b. The sexual state of Phyllosticta was named Guignardia which comprises 353 records in MycoBank (Hyde 1995;Crous et al 1996;.…”
Section: Introductionmentioning
confidence: 99%